National qualifications frameworks in sub-Sahara Africa - Baumann, Fabienne-Agnes [Verfasser] (My University, 2012)
"National qualifications frameworks are currently described as a global phenomenon, a label which accounts for the fact, that frameworks in their different shapes are increasingly subject to policy transfer and thus more and more frameworks are developed in many countries across the globe. The supposed benefits of national qualifications frameworks seem to be convincing, therefore the concept of qualifications frameworks whether national or otherwise in scope, has been greeted with much enthusiasm in literature. Many policy makers perceive national qualifications frameworks as a key driver for reform in the qualifications system, where the latter might be characterized by fragmentation, exclusion of certain groups, a lack of quality assurance or resources, uncoordinated qualification routes, a multitude of providers and awards and so forth. As will be shown in this thesis, unfortunately and not surprisingly there are also downsides to the NQF approach and of course NQFs are not a 'quick-fix' solution. As NQFs apparently appeal especially to developing countries, including many in sub-Sahara Africa, this thesis attempts to analyze national qualifications frameworks policy in sub-Sahara Africa through selected case studies." (Authors' abstract, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.3.1 Afrika; Nationaler Qualifikationsrahmen; Afrika; Subsahara-Afrika; Botswana; Gambia; Namibia; Rwanda; Mauritius; Seychellen